PENGARUH CORPORATE SOCIAL RESPONSIBILITY, GOOD CORPORATE GOVERNANCE, DAN SALES GROWTH TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Pertambangan yang terdaftar di Bursa Efek Indonesia tahun 2021-2023) - Grace Puspita Hasibuan; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2025)
This study aims to provide empirical evidence regarding the effect of corporate social responsibility, good corporate governance, and sales growth on tax avoidance in mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The population in this study were 124 companies, the sample selection used purposive sampling method so that 34 companies were used in this study. This study uses data sourced from financial reports and corporate sustainability reports accessed through the IDX, the company's official website and Bloomberg terminals. The results of this study indicate that the corporate social responsibility variable has a positive effect on tax avoidance, while good corporate governance proxied by independent commissioners and audit committees does not significantly affect tax avoidance, and sales growth has no effect on the level of tax avoidance.